Penerapan Continuous Nitrogen Sealer Guna Meningkatkan Kapabilitas Produk UMKM di Wilayah Malang - Budi Wibowotomo; Oktavia Sulistina; Rachmad Hidayat; Aya Shofia Mufti; Niki Asma’ul Husna (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
This community service program focuses on enhancing the product capability of MSME Wak Ijah. The business faces challenges in its product packaging process, which is still carried out manually using low-quality sealing, resulting in easily damaged product contents and shorter shelf life. In addition, its product marketing is still limited to the Malang area. The methods implemented in this program include training and mentoring through the application of a Continuous Nitrogen Sealer machine, digital marketing training, and the development of product nutrition labeling. The results show a significant improvement in production capacity and product quality, particularly in extending shelf life. To ensure the sustainability of this program’s impact, further mentoring on marketing strategies is required so that the training provided can be consistently and optimally applied in business management.